Exploring the burden and associated risk factors of antenatal depression: a systematic review and meta-analysis - Maurya, Sonia; Sarungbam, Ayuk; Banerjee, Debashmita; Tripathi, Srishti; Kumar, Subhash; Mishra, Sonam; Gupta, Vipin (International Journal Of Community Medicine And Public Health, 2026)
Antenatal depression (AND) is a critical public health issue affecting a significant number of pregnant women worldwide, particularly in low- and middle-income countries. This review synthesizes findings from 40 studies, primarily observational research and randomized controlled trials, published between January 2011 and December 2024, sourced from academic databases including Google Scholar and PubMed. The objective is to explore regional variations in the burden of AND and identify associated risk factors. The evidence reveals that risk factors for AND can be grouped into five categories: family and community dynamics, violence and abuse, obstetric factors, psychological issues, and socio-demographic conditions. Among these, inadequate social support and poor partner relationships consistently emerged as strong predictors. Exposure to violence, especially domestic abuse, significantly increased the risk. Obstetric factors such as unintended pregnancies, high gravidity, and past miscarriages were also linked to higher AND prevalence. In addition, psychological history, including prior episodes of depression or anxiety, played a central role in increasing vulnerability. Socio-demographic elements such as marital status and financial hardship further shaped the risk landscape. These findings emphasize the need for culturally sensitive interventions that strengthen social support networks, address intimate partner violence, and expand access to targeted maternal mental health care.